The Correlation between Motivational Regulation Strategies and Students’ Writing Ability - Hasibuan, Anjani Vicka Prasasti; Ahmad Munir; Widyastuti (Universitas Lancang Kuning, 2024)
The present study looked for kind of motivational regulation strategies used by students with high and low writing ability and found relationship between students’ motivational regulation strategies and writing ability. The method in this study is quantitative with correlational study research design, the subject of the study is 31 English education students in one of state university who took argumentative writing classroom. The questionnaire from Wolters & Benzon (2013a) are used in this study as research instrument of motivational regulation strategies. The result showed different motivational regulation strategies used by students with high writing ability and low writing ability. Students with high writing ability tended to use regulation of value (M=4.04). Furthermore, there is no significant relationship between students’ motivational regulation strategies and their writing ability. Some findings are in line with the research conducted by Wolters & Benzon (2013a) about average of motivational regulation strategies used by students, however, further research in how far motivational regulation strategies affect to students’ writing ability can be conducted by other researchers.